Protective glove use and hygiene habits modify the associations of specific pesticides with Parkinson's disease. (February 2015) - Furlong, Melissa; Tanner, Caroline M.; Goldman, Samuel M.; Bhudhikanok, Grace S.; Blair, Aaron; Chade, Anabel; Comyns, Kathleen; Hoppin, Jane A.; Kasten, Meike; Korell, Monica; Langston, J. William; Marras, Connie; et al.
Abstract: Pesticides have been associated with Parkinson's disease (PD), and protective gloves and workplace hygiene can reduce pesticide exposure. We assessed whether use of gloves and workplace hygiene modified associations between pesticides and PD. The Farming and Movement Evaluation (FAME) study is a nested case–control study within the Agricultural Health Study. Use of protective gloves, other PPE, and hygiene practices were determined by questionnaire (69 cases and 237 controls were included). We considered interactions of gloves and hygiene with ever-use of pesticides for all pesticides with ≥ 5 exposed and unexposed cases and controls in each glove-use stratum (paraquat, permethrin, rotenone, and trifluralin). 61% of respondents consistently used protective gloves and 87% consistently used ≥ 2 hygiene practices. Protective glove use modified the associations of paraquat and permethrin with PD: neither pesticide was associated with PD among protective glove users, while both pesticides were associated with PD among non-users (paraquat OR 3.9 [95% CI 1.3, 11.7], interaction p = 0.15; permethrin OR 4.3 [95% CI 1.2, 15.6] interaction p = 0.05). Rotenone was associated with PD regardless of glove use. Trifluralin was associated with PD among participants who used < 2 hygiene practices (OR 5.5 [95% CI 1.1, 27.1]) but was not associated with PD among participants who used 2 or more practices (interaction p = 0.02). Although sample size was limited in the FAME study, protective glove use and hygiene practices appeared to be important modifiers of the association between pesticides and PD and may reduce risk of PD associated with certain pesticides. Highlights: Associations between occupational pesticide use and PD were modified by work habits. Overall, consistent glove and hygiene use were associated with reduced odds of PD. Among inconsistent glove users, paraquat and permethrin were associated with PD. Among those with inconsistent hygiene habits, trifluralin was associated with PD. Rotenone remained associated with PD regardless of glove use or hygiene habits.